Experience with 808-nm diode laser in the treatment of 47 cases of oral vascular anomalies - Fernanda Vieira HEIMLICH; José Alcides Almeida de ARRUDA; Camila de Nazaré Alves de Oliveira KATO; Leni Verônica de Oliveira SILVA; Leandro Napier SOUZA; Marcus Vinicius Lucas FERREIRA; João de Jesus Viana PINHEIRO; Tarcília Aparecida SILVA; Lucas Guimarães ABREU; Ricardo Alves MESQUITA (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Treatment of oral vascular anomalies (OVA) has focused on minimally invasive techniques rather than radical surgery. We investigated the efficacy and safety of diode laser using the photocoagulation technique in the management of OVA. Forty-seven subjects with OVA were treated with forced dehydration with induced photocoagulation (FDIP) using diode laser (808 nm/4.5 W). This series consisted mostly of male (63.8%) and non-white (63.8%) patients with a mean age of 57.4 years. Varices (91.5%), venous malformations (6.4%), and hemangiomas (2.1%) with a mean size of 7.1 (±4.9) mm were the conditions treated. OVA presented as a nodular lesion (63.8%) involving mainly the lower lip (46.8%). Pulsed laser mode was used as standard and the number of applications varied from one to four sessions, with the majority requiring only one (83%) FDIP session. Kaplan-Meier analysis revealed that complete clinical healing can occur on the 15th day (n=9/29.5%), followed by the 20th (n=6/45.5%), and 30th (n=7/70.5%) days. Postoperative edema was observed in 31 (66%) patients, and recurrence of the lesion occurred in two (4.2%). Based on the data on complete clinical healing, minimal patient discomfort, and satisfactory esthetic results, we can confirm that FDIP by diode laser is a promising candidate for the safe and efficacious treatment of OVA.